MET-04 A case of Brain Metastases with repeated bleeding from Esophageal carcinoma. (28th November 2020) - Mikai, Masataka; Abe, Mitsuyoshi; watanabe, Yo; Nakada, Chie; Huchinoue, Yutaka; Terazono, Sayaka; Uchino, Kei; Ando, Syunpei; Masuda, Hiroyuki; Kondo, Kosuke; Harada, Naoyuki; Miyazaki, Chikao; et al.
Abstract: Brain metastases from esophageal cancer is rare and the incidence has been reported at approximately 5%. We report a case of brain metastases with repeated bleeding from Esophageal carcinoma. The case is a 76-year-old man. Three years ago he was diagnosed with small cell carcinoma of the esophagus by endoscopic biopsy. Metastasis was found only in the cervical lymph node, but the condition was stable by chemoradiotherapy and no metastases were found throughout the body before 1 month. He was admitted to the hospital because of a sudden convulsion, and CT scan revealed cerebral hemorrhage in the right frontal lobe. We performed conservative treatment, but rebleeding was observed from the same site repeatedly after 1 month and 2 months. Due to the influence of bleeding, it was difficult to distinguish cerebral hemorrhage from brain tumor by contrast MRI. After surgery, the cause of bleeding was diagnosed as metastatic brain tumor of esophageal small cell carcinoma. Postoperative radiation therapy was performed in another hospital, but rebleeding was observed 3 months after the operation. A reoperation was performed at another hospital, and a recurrence of metastatic brain tumor was diagnosed. In the case of highly malignant metastatic brain tumors, it was considered necessary to frequently follow the images.